After the Asian crises perspective on global politics and economics - Weber, Maria (Ed) (London Macmillan, 2000)
This book provides comprehensive coverge of the Asian crises from an economic,political and social point of view. This book is divided in two parts.The first includes area studies of the main Asian countries during the crisis,and the Second part of the bo
Keywords: Asia-Politics and government-1945-; Financial crises-Asia; Economics; International relations